Religiosity and human capital formation in the overlapping generation model in Indonesia - Aris Soelistyo (Journal of Innovation in Business and Economics, 2021)
This research aims to determine the extent of the part of spiritual empowerment and the construction of human capital in the overlapping generation model in Indonesia. The study constructs a model by mathematical approach, which ensures the equilibrium of the entire market; use data of the Indonesian region in the 1983-2019 period and the analyzed by regression. Government spending in the fiscal and monetary sector effectively increases the Gross Domestic Product; the influence of labor positively affects the use of capital stock, where the current capital stock is influenced by the stock capital of the previous year. The aspect of government spending has a positive effect on capital stock.